Salinity Stress Is Beneficial to the Accumulation of Chlorogenic Acids in Honeysuckle (Lonicera japonica Thunb.) - Yan, Kun; Cui, Mingxing; Zhao, Shijie; Chen, Xiaobing; Tang, Xiaoli (Frontiers in Plant Science, 2016)
Abstract Honeysuckle (Lonicera japonica Thunb.) is a traditional medicinal plant in China that is particularly rich in chlorogenic acids, which are phenolic compounds with various medicinal properties. This study aimed to examine the effects of salinity stress on accumulation of chlorogenic acids in honeysuckle, through hydroponic experiments and field trials, and to examine the mechanisms underlying the effects. NaCl stress stimulated the transcription of genes encoding key enzymes in the synthesis of chlorogenic acids in leaves; accordingly, the concentrations of chlorogenic acids in leaves were significantly increased under NaCl stress, as was antioxidant activity. Specifically, the total concentration of leaf chlorogenic acids was increased by 145.74% and 50.34% after 30 days of 150 and 300 mM NaCl stress, respectively. Similarly, the concentrations of chlorogenic acids were higher in the leaves of plants in saline, compared with non-saline, plots, with increases in total concentrations of chlorogenic acids of 56.05% and 105.29% in October 2014 and 2015, respectively. Despite leaf biomass reduction, absolute amounts of chlorogenic acids per plant and phenylalanine ammonia-lyase (PAL) activity were significantly increased by soil salinity, confirming that the accumulation of chlorogenic acids in leaves was a result of stimulation of their synthesis under salinity stress. Soil salinity also led to elevated chlorogenic acid concentrations in honeysuckle flower buds, with significant increases in total chlorogenic acids concentration of 22.42% and 25.14% in May 2014 and 2015, respectively. Consistent with biomass reduction, the absolute amounts of chlorogenic acid per plant declined in flower buds of plants exposed to elevated soil salinity, with no significant change in PAL activity. Thus, salinity-induced chlorogenic acid accumulation in flower buds depended on an amplification effect of growth reduction. In conclusion, salinity stress improves the medicinal quality of honeysuckle by promoting accumulation of chlorogenic acids; however, the mechanisms underlying this process were not consistent in flower buds and leaves. Honeysuckle appears to be a promising plant for cultivation in saline land. Our study deepens knowledge of medicinal plant ecology and may provide a guide for developing saline agriculture.